Alcohol, addiction and Christian ethics - Cook, Chris (Christopher C.H.) (Cambridge, UK ; New York : Cambridge University Press, 2006)
Academic perspectives on addictive behaviour usually come from clinical and scientific standpoints, rejecting the 'moral model'. Cook reassesses the nature of addiction and considers the ethical challenges presented by alcohol use and misuse to both individuals and society, arguing that theology should not be excluded from serious discourse about addiction.
Cover; Half-title; Series-title; Title; Copyright; Dedication; Contents; General editor's preface; Preface; 1 Alcohol, addiction and Christian ethics: introduction; 2 An addiction in context: the use, misuse and harmful use of alcohol; 3 Drunkenness as vice in the New Testament; 4 Drunkenness as intemperance: Augustine, Aquinas, Luther and Whitefield; 5 Temperance redefined: the nineteenth-century temperance movement; 6 Addiction as sin and syndrome: the divided self; 7 Alcohol, addiction and Christian ethics; 8 Conclusions; Bibliography; Index of Bible references; Index of names and subjects.
Includes bibliographical references (pages 202-210) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Alcoholism -- Religious aspects -- Christianity; Christian ethics; Compulsive behavior -- Religious aspects -- Christianity; Substance abuse -- Religious aspects -- Christianity; Alcoolisme -- Aspect religieux -- Christianisme; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Alcoholism -- Religious aspects -- Christianity; Christian ethics; Compulsive behavior -- Religious aspects -- Christianity; Substance abuse -- Religious aspects -- Christianity; Alkoholkonsum; Alkoholismus; Christliche Ethik; Alcoholisme; Dronkenschap; Ethische aspecten